Formation of cognitive capacity in Mexico: Economic and public policy impacts - Mayer Foulkes, David; Serván Mori, Edson Enrique (Estudios Económicos de El Colegio de México, 2009)
A stochastic frontier model is used to make a comparative estimate of the production of cognitive capacity and stature in the family, using data from the Mexican survey ENNVIH 2002. We find that child cognitive capacity is associated with the economic status of the family, public policy variables and descriptors of the local economy. Economic and public policy inputs intervene more efficiently for the formation of cognitive capacity that for stature. The application of public programs with the objective of promoting cognitive capacity could be effective.